2013
DOI: 10.1111/eth.12190
|View full text |Cite
|
Sign up to set email alerts
|

Do Parents and Helpers Discriminate between Related and Unrelated Nestlings in the Cooperative Breeding Silver‐Throated Tit?

Abstract: When benefits exceed costs, natural selection may favor adults that develop the ability to recognize and preferentially direct care toward their own offspring to maximize their fitness. Investigations into the ability of adults to recognize offspring in offspring's early development period may help to understand when the ability of kin recognition starts to develop. In birds, studies of offspring recognition have mainly been conducted on bi‐parental breeding species, but relatively seldom on cooperative breedi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…In many bird species with bi-parental care, breeding males have genetically unrelated extra-pair young within their own nest [61][62][63][64], however several studies have shown that such males typically do not appear to discriminate against extrapair young in either feeding or aggression [44,[65][66][67][68]. In this case, the breeding male is the operator, the genetic young are potential targets and the extra-pair young are potential mimics.…”
Section: (B) Parent-offspring Recognition-extra-pair Youngmentioning
confidence: 99%
“…In many bird species with bi-parental care, breeding males have genetically unrelated extra-pair young within their own nest [61][62][63][64], however several studies have shown that such males typically do not appear to discriminate against extrapair young in either feeding or aggression [44,[65][66][67][68]. In this case, the breeding male is the operator, the genetic young are potential targets and the extra-pair young are potential mimics.…”
Section: (B) Parent-offspring Recognition-extra-pair Youngmentioning
confidence: 99%
“…[22][23][24]) and absent in others (e.g. [25][26][27]), and the most probable cause for this difference is the actual risk of parasitism in natural parent-young interactions.…”
Section: Introductionmentioning
confidence: 99%